Implementasi Profil Pelajar Pancasila Dimensi Mandiri di Sekolah Dasar - Fadli, Ridho; Sholeh, Muhammad; Arsil, Arsil (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The Pancasila Student Profile is the spearhead of character development of students, especially in elementary schools today. The implementation of the Pancasila Student Profile can be achieved if educators are able to optimize the stages in its implementation. This study aims to describe the implementation of the independent dimension of the Pancasila Student Profile in elementary schools. This research is qualitative research with a descriptive type. The data in this study was obtained in three ways, namely observation, interviews, and document studies. Data is analyzed by data collection, data presentation and data verification. Test the validity of the data using triangulation techniques. The results of this study show that the independent dimension of the Pancasila student profile has been implemented at SDN 55/I Sridadi, namely understanding the project of strengthening the Pancasila student profile, preparing the school ecosystem, designing projects, managing projects, processing assessments, and reporting project results, to project evaluation and follow-up. At the stage of its implementation, the class teacher takes the most role. The implementation of the independent dimension of the Pancasila student profile has been well implemented through school culture, projects to strengthen the Pancasila student profile, intracurricular learning, extracurricular learning. Schools are expected to maintain the implementation of this implementation well so that it continues to be carried out and remains a routine